Obesity/overweight in functional abdominal pain disorders: high prevalence in children with irritable bowel syndrome - Carvalho, Mary de Assis [UNESP]; Hachem, Andréa Souza [UNESP]; Monterlei, Rafaella Karen Sousa [UNESP]; Penatti, Debora Avellaneda [UNESP]; Dias, Juliana Tedesco [UNESP]; Hashimoto, Miriam [UNESP]; Machado, Nilton Carlos [UNESP] (Springer Nature, 2022)
Purpose: Epidemiologic data reported an association between obesity/overweight and children functional abdominal pain. Aims: To investigate the prevalence of obesity/overweight in children with functional abdominal pain and compare demographics and clinical characteristics between overweight/obesity and normal BMI. Methods: A single tertiary centre, observational retrospective study of consecutive 554 children/adolescents with irritable bowel syndrome (315), abdominal migraine (136), and functional dyspepsia (103), diagnosing according to Rome III and IV criteria. Results: The overall prevalence of obesity/overweight was 35% (irritable bowel syndrome (40%), and different from abdominal migraine (30%, p < 0.04), and functional dyspepsia (28%, p < 0.02). Irritable bowel syndrome BMI z score was higher than abdominal migraine (p < 0.04) and functional dyspepsia (p < 0.002). Baseline characteristics were statistically different in irritable bowel syndrome (number of children, periumbilical pain, anorexia, constipation), abdominal migraine (midline pain, vomiting), and functional dyspepsia (age of pain onset, age at the first visit, epigastric pain, retrosternal pain). There were no statistical differences for all variables comparing obesity/overweight and normal BMI for IBS, AM, and FD children, except for IBS obesity/overweight that was older for the age of pain onset (p < 0.001), age at first visit (p < 0.0001), and more likely to have periumbilical pain (p < 0.02). Additionally, IBS-constipation was the most prevalent subtype (67%) with no difference between obesity/overweight and normal BMI. Conclusions: There is a high proportion of obesity/overweight in functional abdominal pain, predominantly in IBS children, and no difference in demographics and clinical findings between obesity/overweight and normal BMI children during the first visit.
Keywords: Abdominal migraine; Functional abdominal pain; Functional dyspepsia; Functional gastrointestinal disorders; Irritable bowel syndrome; Obesity, Overweight